Construction of a comparative genetic map in faba bean (Vicia faba L.); conservation of genome structure with Lens culinaris - Ellwood, Simon; Phan, Huyen T.T.; Jordan, Megan; Hane, James; Torres, Anna M.; Avila, Carmen M.; Cruz-Izquierdo, Serafin; Oliver, Richard P. (Biomed Central Ltd, 2008)
Background: The development of genetic markers is complex and costly in species with little pre-existing genomic information. Faba bean possesses one of the largest and least studied genomes among cultivated crop plants and no gene-based genetic maps exist. Gene-based orthologous markers allow chromosomal regions and levels of synteny to be characterised between species, reveal phylogenetic relationships and chromosomal evolution, and enable targeted identification of markers for crop breeding. In this study orthologous codominant cross-species markers have been deployed to produce the first exclusively gene-based genetic linkage map of faba bean (Vicia faba), using an F6 population developed from a cross between the lines Vf6 (equina type) and Vf27 (paucijuga type). Results: Of 796 intron-targeted amplified polymorphic (ITAP) markers screened, 151 markers could be used to construct a comparative genetic map. Linkage analysis revealed seven major and five small linkage groups (LGs), one pair and 12 unlinked markers. Each LG was comprised of three to 30 markers and varied in length from 23.6 cM to 324.8 cM. The map spanned a total length of 1685.8 cM. A simple and direct macrosyntenic relationship between faba bean and Medicago truncatula was evident, while faba bean and lentil shared a common rearrangement relative to M. truncatula. One hundred and four of the 127 mapped markers in the 12 LGs, which were previously assigned to M. truncatula genetic and physical maps, were found in regions syntenic between the faba bean and M. truncatula genomes. However chromosomal rearrangements were observed that could explain the difference in chromosome numbers between these three legume species. These rearrangements suggested high conservation of M. truncatula chromosomes 1, 5 and 8; moderate conservation of chromosomes 2, 3, 4 and 7 and no conservation with M. truncatula chromosome 6. Multiple PCR amplicons and comparative mapping were suggestive of small-scale duplication events in faba bean. This study also provides a preliminary indication for finer scale macrosynteny between M. truncatula, lentil and faba bean. Markers originally designed from genes on the same M. truncatula BACs were found to be grouped together in corresponding syntenic areas in lentil and faba bean. Conclusion: Despite the large size of the faba bean genome, comparative mapping did not reveal evidence for polyploidisation, segmental duplication, or significant rearrangements compared to M. truncatula, although a bias in the use of single locus markers may have limited the detection of duplications. Non-coding repetitive DNA or transposable element content provides a possible explanation for the difference in genome sizes. Similar patterns of rearrangements in faba bean and lentil compared to M. truncatula support phylogenetic studies dividing these species into the tribes Viceae and Trifoliae. However, substantial macrosynteny was apparent between faba bean and M. truncatula, with the exception of chromosome 6 where no orthologous markers were found, confirming previous investigations suggesting chromosome 6 is atypical. The composite map, anchored with orthologous markers mapped in M. truncatula, provides a central reference map for future use of genomic and genetic information in faba bean genetic analysis and breeding.